Words within walls: a scoping review of prison-based creative writing - Duursma, Elisabeth (International journal of offender therapy and comparative criminology, 2025)
Creative writing programs offer prisoners a means of self-expression and rehabilitation, fostering self-reflection and emotional expression by encouraging introspection, channelling emotions, building resilience, and fostering creativity and identity. Despite numerous publications on these programs, there is a lack of summaries detailing the types of programs, providers, target audiences, and rigorous evaluation of the benefits. This scoping review examines 56 sources (peer-reviewed, and non-peer reviewed including dissertations, book chapters, and reports) on creative writing initiatives in prisons, focusing on their characteristics and efficacy. Most studies were conducted in the U.S., Australia, and the U.K., with programs mainly run by universities or charitable organizations. Nearly half of the studies did not provide demographic information about participants, and few included evaluations. Evaluations relied on self-reports, observations, and analysis of written works, with minimal use of surveys or interviews. The study highlights the need for more rigorous research to assess the effectiveness of creative writing programs, which have the potential to improve prisoners’ wellbeing during and after imprisonment. Thorough research could demonstrate effectiveness, identify best practices, understand impact, improve programs and inform policy.